Evaluating the evidence on genotoxicity and reproductive toxicity of carbon black: a critical review - Chaudhuri, Ishrat; Fruijtier-Polloth, Claudia; Ngiewih, Yufanyi; Levy, Len (Taylor and Francis, 2017)
Carbon black is produced industrially by the partial combustion or thermal decomposition of gaseous or liquid hydrocarbons under controlled conditions. It is considered a poorly soluble, low toxicity (PSLT) particle. Recently, results from a number of published studies have suggested that carbon black may be directly genotoxic, and that it may also cause reproductive toxicity. Here, we review the evidence from these studies to determine whether carbon black is likely to act as a primary genotoxicant or reproductive toxicant in humans. For the genotoxicity endpoint, the available evidence clearly shows that carbon black does not directly interact with DNA. However, the study results are consistent with the mechanism that, at high enough concentrations, carbon black causes inflammation and oxidative stress in the lung leading to mutations, which is a secondary genotoxic mechanism. For the reproductive toxicity endpoint for carbon black, to date, there are various lung instillation studies and one short-term inhalation study that evaluated a selected number of reproduction endpoints (e.g. gestational and litter parameters) as well as other general endpoints (e.g. gene expression, neurofunction, DNA damage); usually at one time point or using a single dose. It is possible that some of the adverse effects observed in these studies may be the result of non-specific inflammatory effects caused by high exposure doses. An oral gavage study reported no adverse reproductive or developmental effects at the highest dose tested. The overall weight of evidence indicates that carbon black should not be considered a direct genotoxicant or reproductive toxicant.
Keywords: Carbon black; genotoxicity; mutagenicity; mode of action; reactive oxygen species; reproductive toxicity; developmental toxicity